The Doctrine of Tawḥīd and its Practical Manifestation by a Living Sufi Practitioner - Dejan Aždajić (Teosofia: Indonesian Journal of Islamic Mysticism, 2021)
This article explores new pathways of understanding the theological doctrine of tawḥīd from a Sufi theological perspective. It is evident that Sufism has expanded the inherent meaning of tawḥīd from the relatively simple idea of the Oneness of God to the philosophically complex phenomenon that reality is best expressed through an absolute unity of all existence. Instead of engaging in a dialogue about this important doctrinal principle with only written texts, this article intends to combine both traditional sources and the actual voice of one contemporary Sufi practitioner. This original approach aims to circumvent the tendency of a top-down approach to the study of religion, provide a grassroots perspective, and a concrete example of how a theoretical concept can be practically manifested in the life of ordinary believers. Such a contribution is important, for it adds to wider empirical studies of Sufism a localized example that underlines the importance of investigating religion not merely through written texts, but also by a nuanced exploration from the point of view of spiritual seekers themselves. Since Sufis ultimately embark on a spiritual journey and long to attain proximity to God, abstract theory must be met with experiential satisfaction.